Dynamic Combined Optimal Scheduling of Electric Energy and Natural Gas Energy Consumption in Data Center - Xuehui Liu; Guisheng Hou; Lei Yang (Discrete Dynamics in Nature and Society)
Energy consumption is the key factor leading to high operating costs in data center. In this paper, considering the data center service level under the premise of using electricity and gas as energy supply of energy supply and energy consumption from two angles, the data center energy scheduling model is built. The lower model is calculation scheduling model for the data center, and the upper model is data center energy supply scheduling model. Then the particle swarm algorithm is used to simulate the schedule. The results show that using natural gas as supplementary energy supply can effectively reduce the overall energy consumption of data center in considering the service delay level of data center.